Smartphone Data Reveal Neighborhood-Level Racial Disparities in Police Presence - Chen, M. Keith; Christensen, Katherine L.; John, Elicia; Owens, Emily; Zhuo, Yilin (The Review of Economics and Statistics, 2025)
Research on policing has focused on documented actions such as stops and arrests—less is known about patrols and presence. We map the neighborhood movement of nearly 10,000 officers across 21 of America’s largest cities using anonymized smartphone data. Police spend 0.36% more time in neighborhoods for each percentage point increase in Black residents. This neighborhood-level disparity persists after controlling for density, socioeconomic status, and crime-driven demand for policing, and may be lower in cities with more Black police supervisors (but not officers). Patterns of police presence statistically explain 57% of the higher arrest rate in more Black neighborhoods.